A study on the determinants of financial performance of U.S. agricultural cooperatives - Singh, Kuldeep; Misra, Madhvendra; Kumar, Mohit; Tiwari, Vineet (Journal of Business Economics and Management, 2019)
A significant number of studies have been made in the area of agricultural economics; however, there is a paucity of work that investigates factors or determinants which influence the financial performance of agro cooperatives. This paper investigates determinants of financial performance for the United States (U.S.) agricultural cooperatives for the period 2009–2017. By using the United States Department of Agriculture (USDA) database, we created a sample of 37 U.S. agro cooperatives. For analysis, we used panel regression analysis as it is suitable to deal with fixed effect or random effect error component presented in the model. Finding states that the U.S. agro cooperatives are found highly sensitive to economic policy uncertainty. The results provide evidence of a negative relationship between size and profitability. Moreover, the impact of growth and capital intensity is also reflected in the return on asset (ROA). In this study, we considered ROA as a proxy for firm performance. Implications and suggestions for further new research are also discussed.